Aqueductal cerebrospinal fluid pulsatility in healthy individuals is affected by impaired cerebral venous outflow. Issue 5 (8th November 2013) - Beggs, Clive B.; Magnano, Christopher; Shepherd, Simon J.; Marr, Karen; Valnarov, Vesela; Hojnacki, David; Bergsland, Niels; Belov, Pavel; Grisafi, Steven; Dwyer, Michael G.; Carl, Ellen; Weinstock‐Guttman, Bianca; et al.
<x xml:space="preserve">Abstract</x> Purpose To investigate cerebrospinal fluid (CSF) dynamics in the aqueduct of Sylvius (AoS) in chronic cerebrospinal venous insufficiency (CCSVI)‐positive and ‐negative healthy individuals using cine phase contrast imaging. Materials and Methods Fifty‐one healthy individuals (32 CCSVI‐negative and 19 age‐matched CCSVI‐positive subjects) were examined using Doppler sonography (DS). Diagnosis of CCSVI was established if subjects fulfilled ≥2 venous hemodynamic criteria on DS. CSF flow and velocity measures were quantified using a semiautomated method and compared with clinical and routine 3T MRI outcomes. Results CCSVI was associated with increased CSF pulsatility in the AoS. Net positive CSF flow was 32% greater in the CCSVI‐positive group compared with the CCSVI‐negative group (P = 0.008). This was accompanied by a 28% increase in the mean aqueductal characteristic signal (ie, the AoS cross‐sectional area over the cardiac cycle) in the CCSVI‐positive group compared with the CCSVI‐negative group (P = 0.021). Conclusion CSF dynamics are altered in CCSVI‐positive healthy individuals, as demonstrated by increased pulsatility. This is accompanied by enlargement of the AoS, suggesting that structural changes may be occurring in the brain parenchyma of CCSVI‐positive healthy individuals.J. Magn. Reson. Imaging 2014;40:1215–1222. © 2013 Wiley Periodicals, Inc.